Evaluation of biomolecular interactions and cytotoxic activity of organometallic binuclear Ru(II) complexes of ferrocenyl thiosemicarbazones - Khanvilkar, Priyanka; Dash, Soumya R.; Vohra, Alisagar; Devkar, Ranjitsinh; Chakraborty, Debjani (Journal of Biomolecular Structure & Dynamics, 2020)
{Four new ferrocenyl substituted thiosemicarbazone ligands (L1-L4) and their corresponding binuclear ruthenium(II) arene complexes of the general type [(eta(6)-pcym)(L)Ru(mu-im)Ru(L)(eta(6)-p-cym)]Cl (C1-C4) and [(eta(6)-pcym)(L)Ru(mu-azpy)Ru(L)(eta(6)-p-cym)]Cl-2(C5-C8) (cym = cymene
Keywords: binuclear ruthenium(II) complexes; BSA binding interactions; DNA; Ferrocenyl thiosemicarbazone; HeLa human cervical carcinoma

Imidazole/4,4 `-azopyridine bridging binuclear Ru(II) complexes: design, synthesis, bimolecular interactions and cytotoxicity against HeLa cell line - Khanvilkar, Priyanka; Dash, Soumya R.; Pulipaka, Ramadevi; Shirsath, Kavita; Devkar, Ranjitsinh; Chakraborty, Debjani (Journal of the Iranian Chemical Society, 2021)
Binuclear Ru(II)-arene complexes [(eta(6)-pcym)(Flq)Ru(mu-im/mu-azpy)Ru(Flq)(eta(6)-p-cym)]Cl (C1-C8) (cym = cymene; Flq = fluoroquinolones; im = imidazole; azpy = 4,4 ` azo pyridine) have been synthesized and characterized by elemental analysis, molar conductivity and various spectral techniques (ESI-MS, IR, UV-Vis and H-1-NMR). The geometry of the complexes was optimized by DFT calculations, which revealed a pseudo-octahedral coordination around each metal centre. Binding of the synthesized complexes with CT-DNA and BSA was studied spectroscopically, and it has been established that the presence of two hydrophobic planar arene moieties enhances the binding efficacies of the binuclear complexes to the macromolecules, compared to their mononuclear analogues. The results of competitive binding between C1-C8 and ethidium bromide (EB) towards DNA have shown that the complexes are able to displace EB from DNA-EB adduct and interact with DNA via intercalation. The complexes display cytotoxicity against the HeLa human cervical cancer cell lines with IC50 values in the range of 30.1-120.9 mu M.
Keywords: Binuclear ruthenium (II) complexes; BSA binding interactions; DFT calculations; DNA; Fluoroquinolones (FQs); HeLa human cervical carcinoma

Organoruthenium (II) complexes featuring pyrazole-linked thiosemicarbazone ligands: synthesis, DNA/BSA interactions, molecular docking, and cytotoxicity studies - Khanvilkar, Priyanka; Dash, Soumya R.; Banerjee, Devjani; Vohra, Aliasgar; Devkar, Ranjitsinh; Chakraborty, Debjani (Applied Organometallic Chemistry, 2021)
A series of pyrazol-derived thiosemicarbazone ligands (L1-L4) were synthesized and reacted with [Ru(p-cymene)(mu-Cl)Cl](2) to yield a series of ``piano-stool''-type binuclear ruthenium (II)-arene-thiosemicarbazone complexes (C1-C8) of the general type [(Ru(eta(6)-p-cym)L)(2)(mu-im/azpy)] Cl1-2 (L = diphenylpyrazole thiosemicarbazone; cym = p-cymene; im = imidazole; azpy = 4,4 `-azopyridine). The thiosemicarbazone ligands act as N and S donors binding to the Ru(II) center via the imine nitrogen and the thione sulfur atoms. The complexes were characterized by NMR, FTIR, UV-Vis spectroscopy, and ESI+ mass spectrometry. The binding of the complexes to calf thymus deoxyribonucleic acid (CT-DNA) and bovine serum albumin (BSA) was evaluated, and it has been established that the binuclear complexes have good binding efficacies with DNA (K-b = 10(4)-10(5) M-1) and BSA (K-a = 10(5)-10(6) M-1). This is attributed to the arene moieties present in the ligands of the complexes that can have hydrophobic interactions with DNA/BSA. Ethidium bromide (EB) displacement studies and DNA viscosity measurements revealed intercalative interaction of the complexes with DNA. Static interaction of the complexes with BSA was revealed by fluorescence quenching studies. Molecular docking studies confirmed base stacking, H-bonding, and hydrophobic interactions with the biomolecules. In vitro antiproliferative studies of the complexes affirmed that the complexes are cytotoxic towards the HeLa (human cervical cancer) cell line with IC50 values in range of 17.3-41.3 mu M.
Keywords: Binuclear ruthenium (II) complexes; BSA binding interactions; DNA; HeLa human cervical carcinoma; pyrazole-derived thiosemicarbazone